SANKSI PIDANA ANAK ALTERNATIF DALAM PEMBAHARUAN HUKUM PIDANA INDONESIA - BUDIASTUTI, SHINTA RUKMI (Wacana Hukum, 2010)
AbstractsAs an alternative sanction for child, imprisonment should be used as the last option. The non-custodial criminal law can be better alternative for avoiding negative stigma toward children. Key word : alternative sanctions, non custodial.